Եվրոպական միությունը Հայաստանի, Վրաստանի և Մոլդովայի արտաքին քաղաքական օրակարգում մինչև «Արևելյան գործընկերության» մեկնարկը - Հակոբյան, Մհեր (YSU Journal of International Affairs, 2017)
The current article studies the nature and the dynamics of relations between the European Union and three post-Soviet countries, Armenia, Georgia and Moldova, after the collapse of the Soviet Union and their involvement in the European Neighbourhood Policy. In the article, it is attempted to uncover the compliance of the ENP with domestic and foreign political needs of the countries under consideration. Moreover, the article discusses the main mechanisms of transformation, i.e. Europeanization, implemented by the EU.
Keywords: European Union, European Neighbourhood Policy, Action Plan, external governance, Europeanization